(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The objective of the research was to know the implementation of running dictation method in improving students’ ability in writing and students’ motivation during learning through running dictation method. This research used quantitative method with classroom action research (CAR) approach. In this research, it found out that students’ writing ability was improved 47% from first capability. Some of the reasons students are motivated in learning through running dictation method, one of which is because the use of the methods is not boring.